Rasgos alimenticios, reproductivos y potencial productivo del tepezcuintle (Agouti paca) - Montes-Pérez, RC. (Tropicultura, 1997)
The present article reviews the bibliographie date available on the feeding of tepezcuintle (Agouti paca). It also reports about the reproductive rates and the meat production in captivity and mentions some alternatives to improve this characteristics.